Phase II Study of Dasatinib (BMS‐354825) in Patients With Metastatic Adenocarcinoma of the Pancreas. (26th September 2013) - Chee, Cheng Ean; Krishnamurthi, Smitha; Nock, Charles J.; Meropol, Neal J.; Gibbons, Joseph; Fu, PingFu; Bokar, Joseph; Teston, Lois; O'Brien, Timothy; Gudena, Vinay; Reese, Amy; Bergman, Mark; et al.
Abstract : Background: Src, EphA2, and platelet‐derived growth factor receptors α and β are dysregulated in pancreatic ductal adenocarcinoma (PDAC). Dasatinib is an oral multitarget tyrosine kinase inhibitor that targets BCR‐ABL, c‐Src, c‐KIT, platelet‐derived growth factor receptor β, and EphA2. We conducted a phase II, single‐arm study of dasatinib as first‐line therapy in patients with metastatic PDAC. Methods: Dasatinib (100 mg twice a day, later reduced to 70 mg twice a day because of toxicities) was orally administered continuously on a 28‐day cycle. The primary endpoint was overall survival (OS). Response was measured using the Response Evaluation Criteria in Solid Tumors. Circulating tumor cells (CTCs) were also collected. Results: Fifty‐one patients enrolled in this study. The median OS was 4.7 months (95% confidence interval [CI]: 2.8–6.9 months). Median progression‐free survival was 2.1 months (95% CI: 1.6–3.2 months). In 34 evaluable patients, the best response achieved was stable disease in 10 patients (29.4%). One patient had stable disease while on treatment for 20 months. The most common nonhematologic toxicities were fatigue and nausea. Edema and pleural effusions occurred in 29% and 6% of patients, respectively. The number of CTCs did not correlate with survival. Conclusion: Single‐agent dasatinib does not have clinical activity in metastatic PDAC. Abstract : 摘要 背景 . 胰腺导管腺癌（PDAC）中Src、EphA2和血小板衍生生长因子受体α和β水平失调。达沙替尼是一种口服的多靶点酪氨酸激酶抑制剂，靶向作用于BCR‐ABL、c‐Src、c‐KIT、血小板衍生生长因子受体β和EphA2。我们开展了一项达沙替尼一线治疗转移性PDAC患者的II期单臂研究。 方法 . 达沙替尼（100 mg每日2次，后期由于毒性反应减至70 mg每日2次）口服连续给药，28天为一个周期。主要终点为总生存期（OS）。使用实体瘤疗效评价标准（RECIST）评估治疗反应。同时收集循环肿瘤细胞（CTC）。 结果 . 研究入组了51例患者。中位OS为4.7个月[95%可信区间（CI）：2.8 6.9个月]。中位无进展生存期为2.1个月（95%CI：1.6 3.2个月）。34例可评估患者中，有10例（29.4%）患者达到了最佳疗效，病情稳定。1例患者治疗20个月后病情稳定。最常见的非血液学毒性反应为疲乏和恶心。分别有29%和6%的患者出现了水肿和胸腔积液。CTC数量与生存期无关。 结论 . 达沙替尼单药治疗转移性PDAC未显示临床疗效。